The Role of Spirituality against Psychological Distress in University Students: A Focus on Meaning in Life - Anmol Hira; Farah Kanwal; Attiya Majeed (Research Journal of Psychology, 2025)
This study investigates how spirituality affects the psychological distress experienced by university students, with meaning in life acting as a mediating variable. A correlational and quantitative research design was employed, using a purposive sampling technique to select 500 university students from five universities in southern Punjab, Pakistan. Data were collected using validated instruments to measure psychological distress, spirituality, and meaning in life. Statistical analyses, including frequency distribution for demographic variables, correlational analysis, and mediation analysis, were conducted using SPSS. The results revealed a significant negative relationship between spirituality and psychological distress, confirming that meaning in life significantly mediates this relationship. These findings underscore the role of spirituality and meaning in life as protective factors against psychological distress among university students, offering reassurance and hope for their mental well-being. The study concludes by discussing its implications and suggesting directions for future research.